Implementation Of The Spirit Of Achievement And Work Ethic In The Life Of Medan Poltekbang Cadets - Muhammad Raziq Abdul Ilah; Kartika betseba saragih; Muhammad Nabiel; Mikael Angripa Saragi; Mhd.Prassetyo handoko; Jhon Fernando Sijabat; Donna. N.M. Sirait (International Journal of Society and Law, 2024)
The formulation of this research problem is how the influence of motivational spirit and work ethic on the lives of cadets and cadets of the Medan Polytechnic. The research design used in this writing is literature research and field research. The population in this study is all cadets and cadets totaling 10 people. Considering that the number of respondents was less than 100 people to answer the questionnaire that the author distributed and the availability of the author's time as well as for the accuracy of the research results. The types of data used are qualitative data and quantitative data. Data collection techniques are carried out by questionnaires, interviews and documentation. The data analysis technique uses qualitative descriptive analysis and quantitative descriptive analysis. The results of the analysis of multiple linear regression, namely Ŷ=6.518 + 0.827X1 + 0.314X2, mean that there is a positive influence between motivation and work ethic on employee performance. The strength of the relationship between the three variables is strong, which is r = 0.791. From the determination coefficient, it can be explained whether or not employee performance of 62.5% can be explained by motivation and work ethic, while the remaining 37.5% is explained by other factors that are not discussed in this study. From the results of data processing and questionnaire calculations, the author concluded that the motivation and work ethic applied at the Medan Polytechnic had a positive and significant effect on employee performance.